Indonesia’s Settlement Procedure of Small Claims: A Proposal for the Implementation of Online Dispute Resolution - Mubdi, Umar; Trikusrahayu, Martina (Indonesian Journal of Advocacy and Legal Services, 2024)
This research primarily aims to investigate the opportunities for the internalized implementation of Online Dispute Resolution (ODR) within the judicial system for the settlement of small claims in Indonesia. Several positive features of ODR, such as its ease, speed, and cost-effectiveness, can serve as catalysts for the settlement of small claims. Currently, Article 6A of the Supreme Court Regulations No. 4 of 2019 concerning the Settlement Procedure of Small Claims (the Small Claims Regulation) also allows for the use of electronic case administration in accordance with relevant legislation. This study employs a normative juridical research approach with a qualitative descriptive analysis method. The data used consist of secondary data, including primary legal sources from various legislative regulations. Additionally, data from journal articles, reports, and other literature related to ODR and small claims are utilized. A comparative study with the United States is employed to gain insights into best practices for implementing ODR in small claims settlement. Subsequently, this research proposes several steps for the ODR process in resolving simple lawsuits, including case initiation, negotiation, mediation, and adjudication. Furthermore, it emphasizes the principles of ODR that need to be upheld, such as voluntariness, accountability, and impartiality. Ultimately, integrating technology into civil justice systems through ODR will enhance the effectiveness and accessibility of justice in resolving small claims.